Zero-Energy Buildings New Approaches and Technologies - Alberto Pulido Arcas, Jesús; Rubio-Bellido, Carlos; Pérez-Fargallo, Alexis; Oropeza-Perez, Ivan (IntechOpen, 2020)
The building industry is one of the largest energy consumers and countries all over the world are striving to design buildings that satisfy the user's expectations while containing their energy consumption. In this context, zero-energy buildings have emerged as a technological paradigm that can solve this global issue, but its implementation in different contexts has brought a profound debate about its technical, social, and environmental limitations. Thanks to contributions from a variety of scholars from different countries, this book explores different aspects of the zero-energy buildings and gives the reader a broad view of the feasibility of implementation in different contexts.